The Effectiveness of a Training Program to Improve some Aspects of Sensory Integration Disorder and Its Effect on Self-Direction Among a Sample of Children with Intellectual Disabilities (Journal Of Educational and Psychological Researches, 2022)
The present research was conducted to investigate the effectiveness of a training program to improve some aspects of sensory integration disorder and its effect on self-direction among a sample of children with intellectual disabilities. The study sample consists of (10 subjects as an experimental group) were exposed to the training program، and the control group consists of (10 subjects as a control group) were not exposed to the training program. The study included the following tools: A scale of self-direction for intellectual disability (prepared by the researcher). Training program (prepared by the researcher). The Results of the study showed the following: There are no statistically significant differences between the means ranks of the experimental group and the means ranks of the control group (pre the training program) on the sensory integration Scale. There are statistically significant differences between the means ranks of the experimental group and the means ranks of the control group (after the training program) on the sensory integration scale in favor of the experimental group. There are statistically significant differences between the means ranks of the experimental group in the pre-test and the means ranks of the same group in the post-test on the sensory integration scale in favor of the post-test. There are no statistically significant differences between the means ranks of the experimental group in the post-test and the means ranks of the same group in the follow up-test on sensory integration scale. There are no statistically significant differences between the means ranks of the experimental group and the means ranks of the control group (pre the training program) on the self-direction scale. There are statistically significant differences between the means ranks of the experimental group and the means ranks of the control group (after the training program) on the self-direction scale in favor of the experimental group. There are statistically significant differences between the means ranks of the experimental group in the pre-test and the means ranks of the same group in the post-test on the self-direction scale in favor of the post-test. There are no statistically significant differences among the means ranks of the experimental group in the post-test and the means ranks of the same group in the follow up-test on the self-direction scale.